The Incorporation of Fiction in Atra Novel - Selim, Rondek; Heji, Jvan (Humanities Journal of University of Zakho, 2021)
Fiction is one of the basics principles of literature that is present in all literary works, whether poetry or prose. The production of the literary work cannot be made without fiction. Any literary work without fiction will be dull and soulless regardless of how supreme it is. The separation between literary work and fiction is impossible. Fiction is the choice that the writer makes when desiring to escape from the reality and express ideas freely. Fiction is the tool that provides a soul to the literary work, without which the literary works would be nothing but a collection of information or historical texts. This research is under the title (the Incorporation of Fiction in Atra Novel). The novel is a combination of fiction and reality, however, fiction is dominant over reality. Thats is what the researcher attempts to conclude through this research.